2021
DOI: 10.1186/s12863-021-00997-w
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-mir-548 family expression in human reproductive tissues

Abstract: Background Hsa-miR-548ba expressed in ovarian granulosa cells targets PTEN and LIFR, which are essential for ovarian follicle activation and growth. The expression pattern of hsa-miR-548ba correlates with its host gene follicle-stimulating hormone receptor (FSHR), and FSH has a positive influence on hsa-miR-548ba expression. However, hsa-miR-548ba is a member of a large hsa-mir-548 family with potentially overlapping targets. The current study aims to investigate the co-expression of hsa-mir-54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…According to the findings of Peng et al, hsa-miR-8085 is a predicted miRNA that regulates HOXC10 expression, which plays a significant role in ovarian cancer metastasis ( 38 ). The highest expression levels of hsa-miR-548w were discovered in ovarian cumulus granulosa cell (CGC) and mural granulosa cell (MGC) samples according to small RNA high-throughput sequencing performed by Rooda et al ( 39 ). In line with the results of Rooda et al ( 39 ), upregulation of hsa-miR-548w was observed in our study in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of Peng et al, hsa-miR-8085 is a predicted miRNA that regulates HOXC10 expression, which plays a significant role in ovarian cancer metastasis ( 38 ). The highest expression levels of hsa-miR-548w were discovered in ovarian cumulus granulosa cell (CGC) and mural granulosa cell (MGC) samples according to small RNA high-throughput sequencing performed by Rooda et al ( 39 ). In line with the results of Rooda et al ( 39 ), upregulation of hsa-miR-548w was observed in our study in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting micro‐RNA superfamily found altered in the lesion skin of HS patients was the hsa‐miR‐548 family, a large and poorly conserved primate‐specific miRNA family consisting of 76 members 95 . miR‐548a‐3p has been greatly investigated in the past 5 years for its potential to become a screening biomarker for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…94 The microRNA-548 family Another interesting micro-RNA superfamily found altered in the lesion skin of HS patients was the hsa-miR-548 family, a large and poorly conserved primate-specific miRNA family consisting of 76 members. 95 miR-548a-3p has been greatly investigated in the past 5 years for its potential to become a screening biomarker for cancers. It has displayed a relevant possibility to segregate patients with or without prostate cancer, 96 mesothelioma 97 and gastric cancer.…”
Section: Wnt/b-catenin Signallingmentioning
confidence: 99%
“…The substitution T > A of rs221634 causes losing a binding site of hsa-mir-548 family in the 3′ UTR of human LIN28B gene, as analyzed by SNPinfo ( https://manticore.niehs.nih.gov/ ). The hsa-mir-548 family is highly expressed in human reproductive tissues [ 34 ] and is a pivotal suppressor of cell growth [ 35 – 37 ]. So we can also explain our results by that rs221634 T > A polymorphism is the real genetic cause of polyp recurrence.…”
Section: Discussionmentioning
confidence: 99%